2013
DOI: 10.1016/j.jnci.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein α gene expression in Egyptian patients with acute myeloid leukemia

Abstract: We conclude that the majority of the AML patients analyzed, express low levels of C/EBPa mRNA. However, a subset of patients represented by the M3 subtype, express higher levels of C/EBPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
3
9
1
Order By: Relevance
“…In contrast, Kassem et al. () observed decreased levels of CEBPA expression in AML patients (high expression in 27.5% of cases versus low expression in 72.5% of cases) with 63% of high‐level CEBPA expression cases belonging to the M3 subtype (Van Doorn et al., ; Kassem et al., ). The latter study strongly opposes our predictions, which are based on extensive literature wherein the role of these molecules in normal myeloid progenitor differentiation has been described as that of a tumor suppressor/differentiative agent (Krug et al., ; Silva et al., ; Tada et al., ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, Kassem et al. () observed decreased levels of CEBPA expression in AML patients (high expression in 27.5% of cases versus low expression in 72.5% of cases) with 63% of high‐level CEBPA expression cases belonging to the M3 subtype (Van Doorn et al., ; Kassem et al., ). The latter study strongly opposes our predictions, which are based on extensive literature wherein the role of these molecules in normal myeloid progenitor differentiation has been described as that of a tumor suppressor/differentiative agent (Krug et al., ; Silva et al., ; Tada et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…Disruption of CEBPA expression has been reported in the presence of several translocations involving RUNX1 such as t(8;21) RUNX1‐ETO, t(12;21) RUNX1‐TEL, and t(3;21) RUNX1‐EVI1. These translocations specially lead to suppression of CEBPA mRNA expression or CEBPA translation (Grossmann et al., ; Kassem et al., ). Similarly, RUNX1 gene deletions also lead to a reduction in CEBPA expression.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and genetic prognostic markers are important in the classifi cation of leukemia patients. Aberrant chromosomal translocations and gene mutations frequently occur in the transcriptional factor that lead to uncontrolled proliferation of lymphoid and myeloid progenitors (1)(2)(3)(4). The CEBPA gene is a member of the leucine zipper family of the transcription factor family that is essential for the differentiation of myeloid cells (5).…”
Section: Introductionmentioning
confidence: 99%
“…The CEBPA gene located on chromosome 19 q13.1 encodes the basic leucin zipper (bZIP) family of the transcription factors (6). It is expressed at high levels during myeloid cell differentiation and binds to the promoters of multiple specifi c genes at different levels of myeloid linage maturation (2). In AML patients, it was reported that two types of mutations in CEBPA gene exist; N terminal and C terminal (2,5,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation